Kandungan Vitamin C dan Uji Organoleptik Lulur Rosella (Hibiscus sabdariffa L.) - Widyantari, Ni Putu Sukma; wirasiti, Wirasiti; Wahyuni, IGA Sugi (Metamorfosa: Journal of Biological Sciences; Vol 8 No 1 (2021), 2021)
Rosella tea is a ingredient that can be used for making scrubs because of its antioxidant content, but yet limited in cosmetic science. This research was aimed to find out the amount value of vitamin C and antioxidant activity in scrub that contains Rosella tea ( Hibiscus sabdariffa L . ) with variation of rice flour concentrations. This research was conducted at Analitic Laboratory, Faculty of Agricultural Technology and Soil Mechanical Laboratory, Faculty of Engineering, Udayana University from May until August 2018. The experiment was conducted using completely randomized design with seven treatments. Parameters observed were the amount values of vitamin C, antioxidant activities and organoleptic consists texture, colour, aroma and impression of Rosella scrub. The results of this results is the highest vitamin C and antioxidant content were found in rosella scrub with the percentage of 10% white rice flour and 80% red rice flour. The difference in body scrub treatment has a significant effect on proband judgments seen from the texture, color and aroma, while the difference in lulur treatment has no significant effect on proband judgments seen from the impression.   Keyword : scrub, Rosella, vitamin C, antioxidant, organoleptic